The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1017/s0265021505000232
|View full text |Cite
|
Sign up to set email alerts
|

Impact of patient age on propofol consumption during propofol-remifentanil anaesthesia

Abstract: We conclude that with Narcotrend guidance, mean propofol consumption and recovery times are age dependent. However, as a result of large inter-individual variability, age per se does not allow a prediction of individual propofol need or recovery time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…While one study has found women to be more sensitive to the effects of propofol based on lower plasma concentrations required to produce similar bispectral index (BIS) levels 144 , other studies have found no difference 145 or the reverse to be true 146,149 . In the same studies, women required more propofol to achieve the same depth of anaesthesia as monitored by Narcotrend 146,147 . Reduced propofol sensitivity in women is supported by a requirement for more propofol to lose consciousness 5,149,150 and to maintain anaesthesia during surgery 5,149,150 , when adjusted for body weight.…”
Section: Propofolmentioning
confidence: 99%
“…While one study has found women to be more sensitive to the effects of propofol based on lower plasma concentrations required to produce similar bispectral index (BIS) levels 144 , other studies have found no difference 145 or the reverse to be true 146,149 . In the same studies, women required more propofol to achieve the same depth of anaesthesia as monitored by Narcotrend 146,147 . Reduced propofol sensitivity in women is supported by a requirement for more propofol to lose consciousness 5,149,150 and to maintain anaesthesia during surgery 5,149,150 , when adjusted for body weight.…”
Section: Propofolmentioning
confidence: 99%
“…The majority of independent variables did not significantly impact the standing time in this group of horses. Gender and age affect time to awakening in people (Kreuer et al 2005;Buchanan et al 2006), but were not shown to be predictors for standing in this groups of horses. Xylazine has been shown to prolong but improve the quality of recoveries in horses (Santos et al 2003).…”
Section: Discussionmentioning
confidence: 67%
“…The majority of independent variables did not significantly impact the standing time in this group of horses. Gender and age affect time to awakening in people (Kreuer et al. 2005; Buchanan et al.…”
Section: Discussionmentioning
confidence: 99%
“…25 Age has been previously shown to influence intraoperative electrophysiology, but primarily through alteration of anesthetic pharmacokinetics and cortical suppression. 13,[26][27][28][29][30] In our study, the age of the patient did not have any demonstrable effect on the rate of CS localization, quite possibly because our patient population (age range, 7-78 years) did not include very young children or octogenarians.…”
Section: Discussionmentioning
confidence: 97%